2000
DOI: 10.1002/pen.11141
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic in‐line monitoring of polymer extrusion

Abstract: In-line ultrasonic monitoring of polymer co-extrusion and twin-screw extrusion are presented. Co-extrusion of high density polyethylene (HDPE) and a thermoplastic elastomer based on polypropylene-EPDM (ethylene-propylene-diene monomer) has been investigated by ultrasonic sensors consisting of piezoelectric transducers and clad buffer rods. One extremity of the rod (probing end) was installed flush with the die surface so as not to disturb the material flow. The other end was air cooled in order to protect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 6 publications
0
22
0
Order By: Relevance
“…This technique was found useful in monitoring the melt compounding of polymer blends or filled systems (16,17). Ultrasonics have been used to determine the residence time and its distribution in extruders (18,19), to monitor stability of polymer coextrusion (20) and extrusion foaming (21). It was hoped, in the present study, to explore the utility of in-line ultrasound monitoring in the preparation of polystyrene/clay nanocomposites.…”
mentioning
confidence: 99%
“…This technique was found useful in monitoring the melt compounding of polymer blends or filled systems (16,17). Ultrasonics have been used to determine the residence time and its distribution in extruders (18,19), to monitor stability of polymer coextrusion (20) and extrusion foaming (21). It was hoped, in the present study, to explore the utility of in-line ultrasound monitoring in the preparation of polystyrene/clay nanocomposites.…”
mentioning
confidence: 99%
“…A fabrication procedure of the HTUT by a sol gel spray technique is described in [24,25]. Figure 1a presented a sensor insert with the HTUT.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, ultrasonic probe was successfully used [374,375] for on-line process monitoring and Dogan et al [376] showed that this technique has the potential to be imple-mented for in-line polymer melt rheology measurements. Experimental results showed that the viscosity can be measured over nearly one decade of shear rate (1.6 -17 s -1 ) from the measurement of the velocity profile by ultrasonic velocimetry.…”
Section: Rheologymentioning
confidence: 99%